PENTINGNYA MANAJEMEN WAKTU BAGI MAHASISWA DALAM MENINGKATKAN PRESTASI BELAJAR DI SEKOLAH TINGGI TEOLOGI DUTA PANISAL JEMBER - Yuan Xing Grace Hillary Zega; Grace Ester Kurniawati (Metanoia, 2022)
This study aims to provide an understanding to students about the importance of time management for students in improving learning achievement at STT Duta Panisal Jember. By understanding this, students are able to manage time and discipline themselves so that what will be done can be carried out effectively and efficiently. The method used in this thesis is a qualitative research method using a literature study approach, observation, interviews and documentation. On the theoretical basis there is an explanation of what is meant by Understanding Time Management, Understanding Learning Achievement, the Importance of Time Management for Students in Improving Learning Achievement at STT Duta Panisal which is used by researchers as a basis for developing research instruments. The research conducted at the Duta Panisal Theological College campus is in accordance with what has been stated in the title. This research was conducted to all students of STT Duta Panisal. The results of this study are the application of time management for students in improving learning achievement can not be understood properly due to several factors